Hotspots and scientometrics in gallbladder cancer surgery research: a bibliometric and visualization analysis (2014-2024) - Chen, Long-Fei; Bin, Jian-Feng; Zhang, Qin; Li, Han; Chen, Wei; Ge, Hua (Frontiers in Oncology, 2025)
BackgroundGallbladder cancer (GBC) is the most common malignancy of the biliary tract, with significant geographical variations in incidence. The prognosis of GBC is generally poor due to its aggressive nature and late diagnosis. Surgical resection is the only curative treatment, but less than 10% of patients are eligible for radical surgery.MethodsThis study utilized bibliometric analysis and visualization tools to analyze research trends and hotspots in GBC surgery from 2014 to 2024. Data were collected from the Web of Science Core Collection using specific search terms related to GBC and surgical methods. The analysis was performed using tools such as CiteSpace, VOSviewer, and Microsoft Excel to identify key authors, institutions, countries, and research themes.ResultsA total of 479 publications were analyzed, showing a significant increase in research output and citation frequency over the past decade. China and the United States were the leading contributors to GBC surgery research. The analysis revealed six main research clusters, focusing on early diagnosis, surgical techniques, postoperative management, and the application of advanced technologies such as laparoscopic and robotic surgery.ConclusionsThe study highlights the evolution of research priorities in GBC surgery, with a shift towards minimally invasive techniques and comprehensive postoperative management. Future research should emphasize international collaboration and the exploration of emerging technologies to improve patient outcomes.